2003
DOI: 10.1590/s0037-86822003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniose tegumentar americana

Abstract: American cutaneous leishmaniasis is endemic in widespread areas of Latin America. The causative agents include L. (V.) braziliensis, L. (L.) mexicana, L. (V.) panamensis, and related species. The spectrum of disease includes single, localized, cutaneous ulcers, diffuse cutaneous leishmaniasis, and mucosal disease. The main reservoirs for L. (V.) braziliensis and other Leishmania (Vianna) spp. are small forest rodents. The vectors are ground-dwelling or arboreal Lutzomyia sandflies, which are abundant in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
156
0
69

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(240 citation statements)
references
References 22 publications
1
156
0
69
Order By: Relevance
“…On the other hand, the trend towards reduced numbers of occurrences of mucocutaneous leishmaniasis is probably due to better knowledge of the disease, thereby leading to early treatment and accurate diagnosis 13 . Mucous manifestations may appear while cutaneous lesions are still active, or years after the healing, and are usually associated with delayed healing of the primary lesion and inadequate treatment 12 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the trend towards reduced numbers of occurrences of mucocutaneous leishmaniasis is probably due to better knowledge of the disease, thereby leading to early treatment and accurate diagnosis 13 . Mucous manifestations may appear while cutaneous lesions are still active, or years after the healing, and are usually associated with delayed healing of the primary lesion and inadequate treatment 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of pentavalent antimony is contraindicated for pregnant women, because these drugs may cause abortion; these drugs cross the transplacental barrier and may impregnate the nervous tissue of the fetus, leading to severe mental retardation syndromes. In these cases, the treatment involves local care, clinical observation, and the use of amphotericin B 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of IFA in the present study was similar to that found in studies on other endemic areas (Marzochi et al, 1980;Lugo de Yarbuh et al, 1996). Together, the three methods used for ACL diagnosis were able to detect 98.8% of the ACL cases, showing it to be a useful combination for diagnosing the disease (Gontijo, Carvalho, 2003).…”
Section: Discussionmentioning
confidence: 97%